Ultra-Thin Nanocomposite Layers Coated Proppant for improved Compression Strength - Manogran, Johan Suppiah (IRC, 2021)
The main purpose of this research was to design and fabricate an ultrathin resin based nanocomposite layers coated proppant for improved compression strength.